Perancangan User Interface Pura Teluk Terima Dengan Metode Design Thinking - I Nyoman Tri Anindia Putra; Anak Agung Dewi Puspita Sari; Nyoman Trinity Laksmi Maharani (Universitas Binaniaga Indonesia, 2023)
Bali is renowned as a tourist destination with its natural beauty and religious traditions, earning it the nickname